2014
DOI: 10.1590/0001-3765201420140212
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Diabetes and Dyslipidemia in Diabetic Insulin-Resistant Rats by Mangiferin: Role of Adiponectin and TNF-α

Abstract: Mangiferin, present in Mangifera indica bark, was reported to produce hypoglycemic and antidiabetic activity in an animal model of genetic type 2 diabetes and in streptozotocin diabetic rats. Its effect on diabetic insulinresistant animals has not been investigated. The current work aimed to explore the effect of mangiferin on diabetic insulin-resistant rat model. Diabetes was induced by high-fat/high fructose diet for eight weeks followed by a subdiabetogenic dose of streptozotocin (HFD-Fr-STZ). Rats were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 66 publications
2
47
0
4
Order By: Relevance
“…leaf, Rhizoma Anemarrhenae, and Rhizoma Belamcandae. MG has been shown to exert various biological activities and therapeutic effects, including anti-inflammatory [7], anti-oxidative [8], anti-tumor [9] and anti-diabetic effects [10] as well as regulation of metabolism [11]. Recent studies have demonstrated that MG attenuates inflammation in experimental colitis [12], corrects the imbalance of Th17/Treg cells in mice with TNBSinduced colitis [13] and inhibits macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…leaf, Rhizoma Anemarrhenae, and Rhizoma Belamcandae. MG has been shown to exert various biological activities and therapeutic effects, including anti-inflammatory [7], anti-oxidative [8], anti-tumor [9] and anti-diabetic effects [10] as well as regulation of metabolism [11]. Recent studies have demonstrated that MG attenuates inflammation in experimental colitis [12], corrects the imbalance of Th17/Treg cells in mice with TNBSinduced colitis [13] and inhibits macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…The effect may be due to the active molecule MGF, which is present in our mango fruit powder [18]. It has been reported that MGF may ameliorate high-fat diet-induced hepatic TG accumulation and may decrease FFA and TG while increasing plasma beta-hydroxybutyrate levels in rodents [37-39], partly by modulating the expression of genes involved in lipid oxidation and mitochondrial bioenergetics in key metabolic tissues [37-40]. In a randomized, double-blind, controlled trial in humans, MGF supplementation (150 mg/day 12 weeks) improved serum lipid profiles in overweight patients with hyperlipidemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MGF may protect against hyperglycemia, hyperinsulinemia, and insulin resistance in high-fat diet-fed mice [51], in diabetic insulin-resistant rats [37], and in overweight patients [17], as well as against accelerated glucose uptake and utilization in cultured adipocytes and myotubes [51, 52]. However, MGF did not significantly affect fatty acid oxidation even under a high-fat dietary challenge [51].…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged adipocytes and monocyte-derived macrophages alter the expression and secretion of adipokines favoring a pro-inflammatory state, where the production of inflammatory cytokines such as TNF-α and IL-6 is enhanced, while the production of adiponectin, an anti-inflammatory adipokine, is reduced. In this contest, evidence has been provided that in diabetic insulin-resistant rat model mangiferin caused a reduction of serum TNF-α and an elevation of serum adiponectin production as a consequence to PPAR-γ activation [29]. Moreover, mangiferin has also been shown to ameliorate diabetic compliances as cardiomyopathy and nephropathy.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%